Math, asked by anugayu1946, 3 months ago

if x+ y=5 and xy = 4 find x-y using identities ​

Answers

Answered by TrustedAnswerer19
27

Answer:

Given,

 \bf \: x  + y = 5 \:  \:  \: and  \:  \: \: xy = 4 \\  \sf \: x - y =  \: to \: find \:  \\  \bf we \: know \: that \\  \\  \:  \:  \:  \:  \:  \:  \:  \:  \:   \bf \: {(x - y)}^{2}  =  {(x + y)}^{2}  - 4xy \\  \implies \bf \:   {(x - y)}^{2}  =  {5}^{2}  - 4 \times 4 \\ \implies \bf \:  {(x - y)}^{2}  = 25 - 16 = 9 \\ \implies \bf \: x - y =  \sqrt{9}  \\ \implies \bf \: x - y = 3

Additional Information :-

Important identities :-

\boxed{ \bf{ \:  {(x + y)}^{2}  =  {x}^{2}  +  {y}^{2}  + 2xy}}

\boxed{ \bf{ \:  {(x  -  y)}^{2}  =  {x}^{2}  +  {y}^{2}   -  2xy}}

\boxed{ \bf{ \:  {(x  -  y)}^{3}  =  {x}^{3}   -  {y}^{3}   -  3xy(x - y)}}

\boxed{ \bf{ \:  {(x   +  y)}^{3}  =  {x}^{3}    +  {y}^{3}    +   3xy(x  +  y)}}

\boxed{ \bf{ \:  {x}^{2} -  {y}^{2}  = (x - y)(x + y)}}

\boxed{ \bf{ \:  {x}^{3} +  {y}^{3} = (x + y)( {x}^{2}  - xy +  {y}^{2} )}}

\boxed{ \bf{ \:  {x}^{3}  -   {y}^{3} = (x  -  y)( {x}^{2}   +  xy +  {y}^{2} )}}

\boxed{ \bf{ \:  {x}^{4}  -   {y}^{4} = (x  -  y)(x + y)( {x}^{2} +  {y}^{2} )}}

Answered by mathdude500
10

\large\underline{\sf{Given- }}

\red{\rm :\longmapsto\:x + y = 5}

and

\red{\rm :\longmapsto\:xy = 4}

\large\underline{\sf{To\:Find - }}

\boxed{ \bf{ x \:  -  \: y \: using \: suitable \: identity}}

\large\underline{\sf{Solution-}}

Given that

\rm :\longmapsto\:x + y = 5

and

\rm :\longmapsto\:x y = 4

We know,

\red{\rm :\longmapsto\: {(x + y)}^{2}  =  {x}^{2}  +  {y}^{2}  + 2xy -  -  -  - (1)}

and

\red{\rm :\longmapsto\: {(x  -  y)}^{2}  =  {x}^{2}  +  {y}^{2}   - 2xy -  -  -  - (2)}

On Subtracting equation (2) from equation (1), we get

\red{\rm :\longmapsto\: {(x + y)}^{2} -  {(x - y)}^{2} = {x}^{2}+{y}^{2} + 2xy -  {x}^{2} -  {y}^{2} + 2xy}

\red{\rm :\longmapsto\: {(x + y)}^{2} -  {(x - y)}^{2} =4xy}

On substituting the values of x + y and xy, we get

\red{\rm :\longmapsto\: {(5)}^{2} -  {(x - y)}^{2} =4 \times 4}

\red{\rm :\longmapsto\: 25 -  {(x - y)}^{2} =16}

\red{\rm :\longmapsto\: -  {(x - y)}^{2} =16 - 25}

\red{\rm :\longmapsto\: -  {(x - y)}^{2} = - 9}

\red{\rm :\longmapsto\:  {(x - y)}^{2} =  9}

\red{\rm :\longmapsto\:  {x - y} =   \:  \pm \: 3}

Additional Information :-

More Identities to know :-

\blue{\rm :\longmapsto\: {(a + b)}^{2} =  {(a - b)}^{2} + 4ab}

\blue{\rm :\longmapsto\: {(a - b)}^{2} =  {(a  + b)}^{2} - 4ab}

\blue{\rm :\longmapsto\: {(a + b)}^{3} =   {a}^{3}  +  {3a}^{2}b +  {3ab}^{2}  +  {b}^{3}  }

\blue{\rm :\longmapsto\: {(a  -  b)}^{3} =   {a}^{3}  -  {3a}^{2}b +  {3ab}^{2} - {b}^{3}  }

\blue{\rm :\longmapsto\:(a + b)( {a}^{2}  - ab +  {b}^{2}) =  {a}^{3} +  {b}^{3}}

\blue{\rm :\longmapsto\:(a  -  b)( {a}^{2}   + ab +  {b}^{2}) =  {a}^{3} - {b}^{3}}

\blue{\rm :\longmapsto\: {(a + b + c)}^{2} =  {a}^{2} +  {b}^{2} +  {c}^{2} + 2ab + 2bc + 2ca}

\blue{\rm :\longmapsto\: {a + b + c = 0}  \implies \:  {a}^{3} +  {b}^{3} +  {c}^{3} = 3abc }

Similar questions